2008
DOI: 10.1016/j.ijgo.2008.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the number of embryos to transfer following in vitro fertilization

Abstract: Society of Obstetricians and Gynaecologists of Canada. The quality of evidence reported in this document has been described using the Evaluation of Evidence criteria outlined in the Report of the Canadian Task Force on the Periodic Health Exam (Table 1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 145 publications
(269 reference statements)
1
5
0
Order By: Relevance
“…Indeed, there has been a resurgence of interest in NC-IVF for all patients in recent years because it avoids COH and its potential sequelae. Moreover, this also supports the international drive to reduce multiple pregnancies rates with elective single embryo transfer and to minimise complications such as OHSS [ 28 30 ]. Pelinck et al [ 1 ] conducted a systematic review of 1,800 natural IVF cycles reported between 1989 and 2000 and concluded that NC-IVF has a pregnancy rate of less than 10% per cycle.…”
Section: Introductionsupporting
confidence: 55%
“…Indeed, there has been a resurgence of interest in NC-IVF for all patients in recent years because it avoids COH and its potential sequelae. Moreover, this also supports the international drive to reduce multiple pregnancies rates with elective single embryo transfer and to minimise complications such as OHSS [ 28 30 ]. Pelinck et al [ 1 ] conducted a systematic review of 1,800 natural IVF cycles reported between 1989 and 2000 and concluded that NC-IVF has a pregnancy rate of less than 10% per cycle.…”
Section: Introductionsupporting
confidence: 55%
“…Moreover, not only for reducing the OHSS risk, in recent years the amount of FET cycles has dramatically increased due to the trend towards transferring fewer embryos after a fresh IVF cycle, and as a result of improved laboratory techniques [ 134 , 135 ] until to the emerging “freeze-all” policy as an alternative to fresh embryo transfer (ET) to improve IVF outcomes [ 106 ]. A recent prospective, observational, cohort study has suggested that the “freeze-all” policy is advantageous when compared with fresh ETs [ 136 ].…”
Section: Donor And/or Frozen-thawed Cyclesmentioning
confidence: 99%
“…The accumulative success rate could be improved after one ovarian stimulation and retrieval cycle. Therefore, along with the refinement of laboratory techniques, the proportion of FET has increased [7] dramatically since the first baby after the frozen-thawed embryo transfer (FET) cycle was born in 1984 [8, 9]. …”
Section: Introductionmentioning
confidence: 99%